2018
DOI: 10.2131/jts.43.65
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between low midazolam metabolism by cytochrome P450 3A in mice and the high incidence of birth defects

Abstract: -The use of midazolam in early stages of pregnancy has resulted in a high incidence of birth defects; however, the underlying reason is unknown. We investigated expression changes of the CYP3A molecular species and focused on its midazolam metabolizing activity from the foetal period to adulthood. CYP3A16 was the only CYP3A species found to be expressed in the liver during the foetal period. However, CYP3A11 is upregulated in adult mice, but has been found to be downregulated during the foetal period and to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The results revealed that CYP3A16, which has a low metabolic activity in response to pharmaceuticals, is predominantly expressed in the livers of mice during the fetal stage (Kitaoka et al, 2018). We also found that CYP3A11, which has a high metabolic activity, begins to be expressed on postnatal day 7 (Kitaoka et al, 2018). These factors may explain the low level of drug-metabolic activity during the fetal and nursing stages of development.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…The results revealed that CYP3A16, which has a low metabolic activity in response to pharmaceuticals, is predominantly expressed in the livers of mice during the fetal stage (Kitaoka et al, 2018). We also found that CYP3A11, which has a high metabolic activity, begins to be expressed on postnatal day 7 (Kitaoka et al, 2018). These factors may explain the low level of drug-metabolic activity during the fetal and nursing stages of development.…”
Section: Introductionmentioning
confidence: 52%
“…To establish safety measures in such cases, we previously conducted a variety of studies from a pharmacokinetics perspective. The results revealed that CYP3A16, which has a low metabolic activity in response to pharmaceuticals, is predominantly expressed in the livers of mice during the fetal stage (Kitaoka et al, 2018). We also found that CYP3A11, which has a high metabolic activity, begins to be expressed on postnatal day 7 (Kitaoka et al, 2018).…”
Section: Introductionmentioning
confidence: 52%
“…The CBD levels of the fetal brain were similar to those of other organs. We also report that the CYP3A family involved in CBD metabolism is rarely expressed in the fetal liver during this period (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, we felt the need to measure CBD levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning metabolism, CBD is oxidized in the adult liver by cytochrome P450 (CYP) 3A at the 6β, 2′, and 4′ positions (Jiang et al, 2011;Ujvary and Hanus, 2016). However, the metabolic activity of CYP3A is significantly lower in the fetal liver than in the adult liver (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, it is considered that CBD is distributed throughout the entire fetal body with little metabolism in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that variants of Cytochrome P450 (CYPs) are related to the metabolism of neonicotinoids (Shi et al, 2009). Since most CYPs are negligibly expressed in fetal mice, it is expected that fetuses would not possess any capacity for CLO metabolism (Kitaoka et al, 2018). In fact, it is highly unlikely that a fetus could metabolize CLO transferred from the dam because the blood levels of CLO metabolites in the fetus were not higher than those of the dam.…”
Section: Discussionmentioning
confidence: 99%